Business Strategic Plan to Reduce the Non-Performing Loan of a Bank (Case Study at Private Bank in Bandung, West Java) - Novia Lie-29116100, Everlin
Bank ABC is a national bank which facing the problem of high number of Non-Performing Loan from year to year. Since the year of 2014 until 2017, the number of Non-Performing Loan keeps increasing to almost reach the maximum limit which has been set up by the regulation of Otoritas Jasa Keuangan. The maximum limit for NPL rate is as of 5% net. The high number of NPL can affecting the bank’s credibility and reputation. In relation to that issue, it is crucial for Bank ABC to find solution in decreasing and overcoming NPL’s problem. This thesis intends to help Bank ABC to overcome NPL’s problem, by taking samples of 30 NPL’s debtors from each group of Commercial Loans and SME Loans. Author then calculates all of data samples from each group using calculation of Altman Z-Score Theory and Time Interest Earned. Author also conducted calculation using US Index as a supplement method of analysis. The financial reports gathered for data process of each debtor are on the year of 2014, 2015, and 2016. In its theory, The Altman Z-Score is a tool used in credit analysis that includes few financial ratios at a time (profitability, leverage, liquidity, solvency and activity ratio) to predict whether a company has a high degree of probability of being insolvent. The theory of Time Interest Earned uses the calculation of Earnings before Interest and Taxes, divided by interest charges. The calculation is used to determine to what extend debtor is able to fulfill its obligation to bank, using its business income. Meanwhile, US Index is can be used as a tool to determine debtor’s capacity to be given loan at bank. It is also recommended that Bank ABC should asses the debtors and charge interest rates accordingly, as ineffective interest rate policy can increase the level of interest rates and consequently NPL. The central bank should apply stringent regulations on interest rates charged by banks as to regulate their interest rate spread. Bank should apply efficient and effective credit risk management that will ensure that loans are matched with ability to repay, no or minimal insider lending, loan defaults are projected accordingly and relevant measures taken to minimize the same.